2018
DOI: 10.1177/0739456x18755495
|View full text |Cite
|
Sign up to set email alerts
|

When Context Meets Self-Selection: The Built Environment–Travel Connection Revisited

Abstract: Existing studies on the built environment (BE)–travel connection tend to underestimate the potential of BE-based mobility strategies due to these studies’ limitations in conceptual and analytical frames. This study conceptualized the combined direct and indirect effects of BE on travel as contextual effects around three features of BE: multiplicity, interaction, and scalability. The conceptual framework was operationalized through multilevel modeling. The empirical analysis from Austin, Texas, verified the mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 58 publications
(75 reference statements)
1
10
0
Order By: Relevance
“…Further research might also include gender as a control variable. Finally, more advanced multivariate models also considering interaction effects between variables could provide a more accurate understanding of how built environment factors interact with behavioral choices and preferences, following models proposed in extant research [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further research might also include gender as a control variable. Finally, more advanced multivariate models also considering interaction effects between variables could provide a more accurate understanding of how built environment factors interact with behavioral choices and preferences, following models proposed in extant research [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Naess (2009Naess ( , 2014 and Levine (1999) argue that the phenomenon of RSS itself shows that the BE has an impact on travel behavior. If people have preferences for specific modes and residential areas, they should be provided with the "right" environment, to allow them to travel by, for example, public transport or active modes, and to reduce travel by personal vehicles (Zhang and Zhang, 2018). Providing the "right" BE reduces residential dissonance (see, for example, De Vos et al, 2012;Frank et al, 2007;Huang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings, higher levels of land use mix associated with less decline of walking mobility at an area level, would justify recommending diverse land use, as they suggest that such initiatives may benefit health of the area where they are implemented (if not individuals in the area). This further highlights the importance of selecting a proper spatial unit of analysis in examining contextual effects, as environmental strategies to influence outcomes of interest are implemented at different scales [38]. The outcome of the study was self-reported difficulty in walking and climbing stairs.…”
Section: Discussionmentioning
confidence: 99%